The Association between Sociodemographic and Health Characteristics with the Attendance Rate of the Elderly School of Darun Najah, Sambak Village, Kajoran District - Ayu Fadhila; Akhmal Raziq Kharazi (International Journal Of Health Science, 2025)
The United Nations states that the elderly population is increasing globally annually, from 771 million to 830 million people, accounting for 10 to 10,5% respectively. In Indonesia, the Central Bureau of Statistics reported the rise of the elderly population from 9,92% of the population in 2020 to 11,75% in 2023. Specifically in the Province of Central Java, the percentage of elderly population increases from 13,07% to 13,50% between 2022 and 2023. The rise of the elderly population could potentially pose a challenge to public development as they are often vulnerable and dependent, facing health and socioeconomic challenges. In order to combat this, the Government of Indonesia formed elderly schools, an educational and social program that aims to empower the elderly. This study aims to analyze the association between sociodemographic and health characteristic factors and the attendance rate of one of the elderly schools located in Central Java called The Elderly School of Darun Najah, Sambak Village, Kajoran District. This study uses an analytical observational quantitative approach with a cross-sectional design. Sampling is conducted using a total sampling design resulting in 40 respondents. Data analysis is conducted in univariate and bivariate (chi-square and fisher's exact test) methods. Significant factors (p-value<0,05) of the attendance rate of the elderly school include age, sex, marital status, and employment status, while blood pressure and body mass index are not significant (p-value>0,05). This study recommends that elderly school administrators provide personalized facilities and activities that cater to their participants' characteristics.